2020
DOI: 10.1109/tvt.2020.2966787
|View full text |Cite
|
Sign up to set email alerts
|

Joint OAM Multiplexing and OFDM in Sparse Multipath Environments

Abstract: The emerging orbital angular momentum (OAM) based wireless communications are expected to be a high spectrum-efficiency communication paradigm to solve the growing transmission data rate and limited bandwidth problem. Academic researchers mainly concentrate on the OAM-based line-of-sight (LoS) communications. However, there exist some surroundings around the transceiver in most practical wireless communication scenarios, thus forming multipath transmission. In this paper, a hybrid orthogonal division multiplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 33 publications
(25 reference statements)
0
29
0
Order By: Relevance
“…Moreover, the novel multiplexing and coding of orbital angular momentum (OAM) waves provide a new degree of freedom to realize ultra-high capacity communication [114]. The channel model of an OAM beam at 70 GHz was presented in [115], while an OAM multipath channel model based on uniform circle array in the mmWave band was reported in [116]. Despite the increasing attentions on using the OAM technique in the THz band [117,118], the research on THz OAM is still underdeveloped due to the huge challenges in the generation and detection of THz vortex beam.…”
Section: Other Channel Modelsmentioning
confidence: 99%
“…Moreover, the novel multiplexing and coding of orbital angular momentum (OAM) waves provide a new degree of freedom to realize ultra-high capacity communication [114]. The channel model of an OAM beam at 70 GHz was presented in [115], while an OAM multipath channel model based on uniform circle array in the mmWave band was reported in [116]. Despite the increasing attentions on using the OAM technique in the THz band [117,118], the research on THz OAM is still underdeveloped due to the huge challenges in the generation and detection of THz vortex beam.…”
Section: Other Channel Modelsmentioning
confidence: 99%
“…Similarly, they assumed that the OAM-based wireless channel model in sparse multipath environments was known and that there was no inter-mode interference caused by reflection paths. On the basis of previous research, Liang et al built an OAM-based wireless channel model in a sparse multipath environment including a LOS path and several reflection paths, which obtained high capacity while resisting multipath interference [83].…”
Section: Combination Of Oam and New Technologiesmentioning
confidence: 99%
“…Fortunately, we have noticed that the anti-multipath property of orthogonal frequency division multiplexing (OFDM) technique can be utilized to mitigate the inter-symbol interference or the channel crosstalk for broadband wireless communications. The compatibility between OAM and the traditional OFDM has been proven, which can achieve extremely high capacity in OAM communications [18][19][20][21]. The experimental investigation has been presented to indicate the inter-symbol interference caused by multipath effects for OAM channel using OFDM, and the results have demonstrated that an channel with high order OAM-modes tends to suffer from stronger intra-and inter-channel crosstalk [18].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the overhead in hardware and the computational complexity in software, the researchers of [20] proposed a time-switched OFDM-OAM MIMO system by performing a time-switched sequence in the baseband, and analyzed spectrum efficiency for LoS OAM wireless transmissions. The authors have proposed the joint OAM multiplexing and the traditional OFDM scheme in sparse multipath environments, and demonstrated that the phase difference compensation can drastically increase channel capacity [21].…”
Section: Introductionmentioning
confidence: 99%